Teaching and doing anti-criminology: An autoethnography of transgressive pedagogies - Colaguori, Claudio (Contemporary justice review, 2022)
As both first-generation, working-class Canadians from Italian immigrant families we were very much outsiders to the academy when we began our respective university studies in the late 1980s. Today, as third-generation critical criminologists, we strive to bring an intersectional perspective to the classroom and to likewise enable marginalized students to find their voice and position themselves as active subjects, not objects of others’ inquiry. From sharing the insights offered by Left Realism and Zemiology the authors offer an autoethnographic account of teaching crime and justice. In keeping with hooks’ observation that the reality of class differences is starkly revealed in educational settings, this paper seeks to explore the intersections between teaching and learning as a process that involves existential self-reflection towards a critical pedagogy aimed at creating an inclusive teaching and learning space that challenges myths, demythologize power relations, and promotes social justice.